Photoacoustic effect of azo derivatives modified by click reagents and parceled by liposomes. (January 2020) - Yang, Libin; Li, Liaoliao; Gao, Hong; Wang, Dong; Yang, Zhou; Cao, Hui; He, Wanli
Abstract: Photoacoustic (PA) imaging has been highlighted as one of the latest and the most promising biophotonic diagnostic modalities. As promising contrast agents, near-infrared (NIR) light-absorbing agents are highly in great demand. Here, the PA and photothermal (PT) effects of a series of NIR absorbing azo derivatives were characterized. Interestingly, compared with tetracyanoethylene (TCNE) and 7, 7, 8, 8-tetracyanoquiodimethane (TCNQ), the click reagent 2, 3, 5, 6-tetrafluoro-7, 7, 8, 8-tetracyanoquiodimethane (F4 -TCNQ) caused the red shift to near infrared (NIR) region for the peaks of PA intensity of molecules. Moreover, symmetrical molecular structure of NIR dyes had better PA effect. The M2a (clicked by TCNQ) molecules were embedded into hydrophobic phospholipid bilayer of liposomes (M2a⊂L) and internalized into human breast cancer Michigan Cancer Foundation-7 (MCF-7) cell. The toxicity of the cell was low, because the cell viability reached amost 100%, which was evaluated through CCK-8 assays to determine the metabolic viability of MCF-7 cells, while the cell PA intensity was high (1.5 × 10 3 ). The systematical research of the NIR dyes not only provided a series promising NIR dyes for imaging and treatment, but also guided the design of contrast agents and PT agents which had high PA and PT effects. Graphical abstract: The click reagent F4-TCNQ caused the red shift to NIR region for the peaks of PA intensity of molecules.Image 1 Highlights: Azo derivatives clicked by click reagents could be good contrast agents and PT agents. Dye in hydrophobic phospholipid bilayer of liposomes showed good stability, high PA intensity and low toxicity. Click reagent F4-TCNQ caused the red shift to near infrared (NIR) region for the peaks of PA intensity of molecules. Symmetrical molecular structure of NIR dyes had better PA effect.